Hubungan Tingkat Pengetahuan Orang Tua Dengan Kepatuhan Minum Obat Anti Tuberkulosis Anak Di RSUD Dr.H. Abdul Moeloek Provinsi Lampung Tahun 2025 - Avrilia, Wanda; Setiawati; Winarno , Rudi; Nirwanto (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Background: Tuberculosis is a chronic disease caused by the bacteria Mycobacterium tuberculosis. This type of bacteria is commonly called acid-fast bacteria (AFB) because it is composed of rods and is acid-fast. Generally speaking, most pathogenic tuberculosis worsens the lung parenchyma and causes parenchymal tuberculosis. However, these bacteria also have the ability to infect other organs of the body (extrapulmonary TB), such as the pleura, glands, bones, and other organs. Objective: To determine the relationship between the level of knowledge and compliance in taking anti-tuberculosis drugs in TB patients at Dr. H. Abdul Moeloek Regional Hospital, Lampung Province. Method: This type of research is a type of quantitative research using the analytical survey method. Analytical survey research is a study that tries to find out why health problems can occur, then analyzes the relationship between risk factors (factors that influence the effect) and effect factors (factors influenced by risk). With correlation analysis to find out how far the risk factor contributes to the effect or an event of a health problem, so that in analytical research a research hypothesis and statistical test are needed. Results: Based on the results of the chi-square test that has been carried out, a p-value of 0.000 < 0.05 was obtained. Conclusion: There is a relationship between the level of parental knowledge and compliance with taking anti-tuberculosis drugs for children at Dr.H.Abdul Moeloek Hospital, Lampung Province in 2025